2001
DOI: 10.1046/j.1523-1747.2001.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal H2O2 Accumulation Alters Tetrahydrobiopterin (6BH4) Recycling in Vitiligo: Identification of a General Mechanism in Regulation of All 6BH4-Dependent Processes?

Abstract: It has been shown in vivo that patients with the depigmentation disorder vitiligo accumulate hydrogen peroxide (H(2)O(2)) accompanied by low catalase levels and high concentrations of 6- and 7-biopterin in their epidermis. Earlier it was demonstrated that epidermal 4a-OH-tetrahydrobiopterin dehydratase, an important enzyme in the recycling process of 6(R)-L-erythro 5,6,7,8 tetrahydrobiopterin (6BH(4)), has extremely low activities in these patients concomitant with a build-up of the abiogenic 7-isomer (7BH(4))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
152
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 51 publications
2
152
0
1
Order By: Relevance
“…High 7BH 4 levels were also found in the epidermis of patients with the depigmentation disorder, vitiligo (Schallreuter et al 1994a,b). In the latter case, it was shown that these high levels are based on deactivation of the enzyme PCD due to accumulation of H 2 O 2 in the 10 3 M range (Schallreuter et al 2001). Taken together, a role for 7BH 4 in the pathophysiology of these two diseases has been proved.…”
Section: Introductionmentioning
confidence: 89%
“…High 7BH 4 levels were also found in the epidermis of patients with the depigmentation disorder, vitiligo (Schallreuter et al 1994a,b). In the latter case, it was shown that these high levels are based on deactivation of the enzyme PCD due to accumulation of H 2 O 2 in the 10 3 M range (Schallreuter et al 2001). Taken together, a role for 7BH 4 in the pathophysiology of these two diseases has been proved.…”
Section: Introductionmentioning
confidence: 89%
“…1). Complex interactions between pterin metabolism, melanin and catecholamine synthesis may be abnormally mediated by H 2 O 2 in NSV (70). Based on recent studies of mononuclear cells in the sera of patients with NSV, Picardo's group suggested that mitochondria might be an unifying target of reactive oxygen species generation, cytokine production, catecholamine release, alteration of Ca 2+ metabolism leading to melanocyte loss (59).…”
Section: Melanocyte Destructionmentioning
confidence: 99%
“…In vitiligo, a skin disorder characterized by a defective protection against UV radiation due to the acquired loss of constitutional pigmentation [19], H 4 Bip metabolism is altered [20]. Dihydro and oxidized pterin derivatives accumulate in the affected tissues at concentrations that are significantly higher than those reported for healthy cells [20,21]. Although intracellular concentrations were not determined, it can be assumed that pterins can reach any cellular compartment since these compounds can freely cross phospholipid membranes [22].…”
Section: Introductionmentioning
confidence: 99%